2023
DOI: 10.1039/d2bm01881k
|View full text |Cite
|
Sign up to set email alerts
|

Injectable thermosensitive hydrogel to modulate tolerogenic dendritic cells under hyperglycemic condition

Abstract: Scaffolds and hydrogels can deliver therapeutic or immunomodulatory agents to regulate the bone healing in periodontal inflammation. Hyperglycemia associated with diabetes mellitus is a significant risk factor for periodontitis as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…71 Similarly, Zhu et al prepared a thermosensitive injectable self-assembled hydrogel (TISH) using chitosan which could transition from liquid phase to gelation phase upon incubation at 37 °C. 78 This hydrogel was loaded with resveratrol and granulocyte-macrophage colony-stimulating factor (GM-CSF) to release the bioactive molecules to induce tolerogenic dendritic cells and regulatory T-cells, and finally attenuate diabetic periodontitis.…”
Section: Fabrication Of Injectable Hydrogelsmentioning
confidence: 99%
“…71 Similarly, Zhu et al prepared a thermosensitive injectable self-assembled hydrogel (TISH) using chitosan which could transition from liquid phase to gelation phase upon incubation at 37 °C. 78 This hydrogel was loaded with resveratrol and granulocyte-macrophage colony-stimulating factor (GM-CSF) to release the bioactive molecules to induce tolerogenic dendritic cells and regulatory T-cells, and finally attenuate diabetic periodontitis.…”
Section: Fabrication Of Injectable Hydrogelsmentioning
confidence: 99%
“…designed a thermosensitive injectable chitosan‐based hydrogel for controlled and sustained delivery of GM‐CSF and resveratrol to modulate DCs toward a tolerogenic phenotype. [ 174 ] DCs showed increased tolerogenic genes (e.g., FOXP3 , SOCS3 , TGF‐β , IL‐10 ) and decreased maturation and activation genes (e.g., CD80 , CD83 , CD86 ) when cultured with the hydrogel in vitro under hyperglycemic condition. The co‐culture experiment found that tolerogenic DCs could promote the differentiation of naive T cells to regulatory T cells.…”
Section: Bioactive Hydrogels For Periodontitis Treatmentmentioning
confidence: 99%
“…Anti-inflammatory [174] Figure 6. The anti-inflammatory effects of the chitosan/β-GP/gelatin-based hydrogel loaded with aspirin and erythropoietin.…”
Section: Mouse Subcutaneous Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, some researchers have emphasized the control of tissue inflammation and immunomodulation, potentially neglecting the fact that the ultimate aim of periodontal therapy is to promote the regeneration of periodontal tissue. [17][18][19] Secondly, traditional hydrogels often exhibit suboptimal biomechanical properties, making them susceptible to damage from external forces when applied to periodontal tissue. 20,21 In recent years, incorporating nanosized particles or other bioactive materials, as well as increasing the hydrogel polymer concentration or crosslink density, have been commonly employed as major strategies to enhance mechanical property.…”
Section: Introductionmentioning
confidence: 99%